Retrospective Poe
XXXII, 323 p. 12 illus.
Keywords: This book analyzes a range of Edgar Allan Poe’s writing, focusing on new readings that engage with classical and (post)modern studies of his work and the troubling literary relationship that he had with T.S. Eliot. Whilst the book examines Poe’s influence in Spain, and how his figure has been marketed to young and adult Spanish reading audiences, it also explores the profound impact that Poe had on other audiences, such as in America, Greece, and Japan, from the nineteenth to the twenty-first century. The essays attest to Poe’s well-deserved reputation, his worldwide legacy, and his continued presence in global literature. This book will appeal particularly to university teachers, Poe scholars, graduate students, and general readers interested in Poe’s oeuvre. José R. Ibáñez is Assistant Professor at the University of Almeria, Spain. He has published articles and book chapters on Comparative literature and American literature, with an emphasis on Edgar Allan Poe and the short fiction of Southern United States authors and hyphenated American authors, such as Jhumpa Lahiri and Ha Jin. Santiago Rodríguez Guerrero-Strachan is Senior Lecturer at the University of Valladolid, Spain. He has published extensively on the relations between Spanish and American literatures and on the short story. His research interests include American literature of the Romantic and Modernist periods.